Human Immunodeficiency Virus Type 1 Persistence Following Systemic Chemotherapy for Malignancy. (3rd June 2017) - Henrich, Timothy J; Hobbs, Kristen S; Hanhauser, Emily; Scully, Eileen; Hogan, Louise E; Robles, Yvonne P; Leadabrand, Kaitlyn S; Marty, Francisco M; Palmer, Christine D; Jost, Stephanie; Körner, Christian; Li, Jonathan Z; et al.
Summary: Systemic chemotherapy for various malignancies leads to long-term increases in CD4 + T-cell–associated HIV-1 RNA and DNA burden in some individuals. HIV-infected cytomegalovirus/Epstein-Barr virus–specific CD4 + T cells may also contribute to maintenance of the HIV DNA reservoir following chemotherapy. Abstract: Background: Systemic chemotherapies for various malignancies have been shown to significantly, yet transiently, decrease numbers of CD4 + T lymphocytes, a major reservoir for human immunodeficiency virus type 1 (HIV-1) infection. However, little is known about the impact of cytoreductive chemotherapy on HIV-1 reservoir dynamics, persistence, and immune responses. Methods: We investigated the changes in peripheral CD4 + T-cell–associated HIV-1 DNA and RNA levels, lymphocyte activation, viral population structure, and virus-specific immune responses in a longitudinal cohort of 15 HIV-1–infected individuals receiving systemic chemotherapy or subsequent autologous stem cell transplantation for treatment of hematological malignancies and solid tumors. Results: Despite a transient reduction in CD4 + T cells capable of harboring HIV-1, a 1.7- and 3.3-fold increase in mean CD4 + T-cell–associated HIV-1 RNA and DNA, respectively, were observed months following completion of chemotherapy in individuals on antiretroviral therapy. We also observed changes in CD4 + T-cell population diversity and clonal viral sequence expansion during CD4 + T-cell reconstitution following chemotherapy cessation. Finally, HIV-1 DNA was preferentially, and in some cases exclusively, detected in cytomegalovirus (CMV)– and Epstein-Barr virus (EBV)–responsive CD4 + T cells following chemotherapy. Conclusions: Expansion of HIV-infected CMV/EBV-specific CD4 + T cells may contribute to maintenance of the HIV DNA reservoir following chemotherapy.